2012
DOI: 10.1016/j.polymdegradstab.2012.03.003
|View full text |Cite
|
Sign up to set email alerts
|

A new kinetic model for predicting polyamide 6-6 hydrolysis and its mechanical embrittlement

Abstract: PA 6-6 hydrolysis at 60, 70, 80 and 90 C in distilled water has been studied by Fourier transform infrared spectroscopy, viscometry in molten state, differential scanning calorimetry and uniaxial tensile testing. The molar mass decreases sharply from the early periods of exposure to reach an equilibrium value of about M nE z 10À11 kg mol À1 almost temperature independent. Hydrolytic chain scissions destroy the entanglement network in the amorphous phase and liberate small macromolecular segments which rearrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 41 publications
3
43
0
Order By: Relevance
“…The polymer has significant chain-chain interaction arising from hydrogen bonds between the adjacent amide groups 23. It is generally accepted that the polyamides are strongly resistant to chemical agents due to high degree of crystallinity 222528. Thus, they are hard to react with monomers and resin primers of relining materials.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The polymer has significant chain-chain interaction arising from hydrogen bonds between the adjacent amide groups 23. It is generally accepted that the polyamides are strongly resistant to chemical agents due to high degree of crystallinity 222528. Thus, they are hard to react with monomers and resin primers of relining materials.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrolytic breakdown of amide bonds in strong acids is problematic since it would lead to relative decrease in molecular weight of the polymer, severe destruction, and loss of surface integrity 2228. Moreover, the rate constant of acid hydrolysis depends on acid concentration; in the presence of concentrated acids, the reaction rate is decreased due to reduced water activity 202225. Hocker et al24 showed that the rate of polyamide hydrolysis in solutions containing small weak organic acid was twice that of a water hydrochloric acid solution at the same pH.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…belong to this category. then, the reverse reaction cannot be neglected and the kinetic model is somewhat more complicated (Jacques et al, 2002;El Mazry et al, 2012), especially when acids are present (Merdas et al, 2003). it can be easily shown that the equilibrium molar mass M We (when t AE •) is given by:…”
Section: Mechanisms Of Chemical Ageing: Hydrolytic Processesmentioning
confidence: 99%